2017
DOI: 10.3390/nu9040326
|View full text |Cite
|
Sign up to set email alerts
|

Intake and Dietary Food Sources of Fibre in Spain: Differences with Regard to the Prevalence of Excess Body Weight and Abdominal Obesity in Adults of the ANIBES Study

Abstract: The aim was to study the intake and food sources of fibre in a representative sample of Spanish adults and to analyse its association with excess body weight and abdominal obesity. A sample of 1655 adults (18–64 years) from the ANIBES (“Anthropometric data, macronutrients and micronutrients intake, practice of physical activity, socioeconomic data and lifestyles”) cross-sectional study was analysed. Fibre intake and dietary food sources were determined by using a three-day dietary record. Misreporters were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
2
12
1
2
Order By: Relevance
“…The association between fibre intake and age are in line with studies from the U.S., Germany, and Ireland, which found that adolescents consumed less fibre than younger children [ 31 , 32 ], and that younger adults consumed less total fibre than older adults [ 33 ], after adjusting for energy intake. Whilst men typically have higher unadjusted fibre intakes than women [ 13 ], studies in Spain [ 34 ], Ireland [ 33 ], Italy [ 35 ], and Finland [ 36 ] revealed that men had lower intakes of fibre than women when adjusted for energy intake. Other recent analyses from the 2011–2012 NNPAS have reported that, when adjusted for energy intake, these groups generally have lower intakes of core foods and higher intakes of discretionary foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between fibre intake and age are in line with studies from the U.S., Germany, and Ireland, which found that adolescents consumed less fibre than younger children [ 31 , 32 ], and that younger adults consumed less total fibre than older adults [ 33 ], after adjusting for energy intake. Whilst men typically have higher unadjusted fibre intakes than women [ 13 ], studies in Spain [ 34 ], Ireland [ 33 ], Italy [ 35 ], and Finland [ 36 ] revealed that men had lower intakes of fibre than women when adjusted for energy intake. Other recent analyses from the 2011–2012 NNPAS have reported that, when adjusted for energy intake, these groups generally have lower intakes of core foods and higher intakes of discretionary foods.…”
Section: Discussionmentioning
confidence: 99%
“…The associations may also be influenced by under- and over-reporting. A recent study reported that fibre intake among Spanish adults was lower among overweight and obese, but when under- and over-reporters were excluded, these differences were no longer observed [ 34 ]. High-fibre foods contain other nutrients and non-nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Among chronic diseases associated with economic development, obesity is one of the most serious public health problems [ 70 ], and fiber is associated with satiety [ 26 , 27 ]. Therefore, the relationship between fiber intake and excess weight is of great interest [ 34 , 55 , 85 ], especially since we know that younger adults are now gaining weight at a faster rate than the generation of their parents [ 93 ]. In this sense, our work confirms the effect of economic development on BMI since the prevalence of people with a BMI above the normal range (obese and overweight) was significantly lower in Tunisian participants than in American ones.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits are related to the complex function of fiber as a carrier of phytochemicals and its effect on gut microbiota [ 28 , 29 , 30 , 31 ]. Recent studies evidence that further knowledge of fiber healthy properties requires including information about food sources [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the appropriate single weight for all users is a difficult process as weight gain has recently been reported all over the world. In many countries, population weight gain is seen as part of the global obesity epidemic [2][3][4][5][6][7][8]. Data from 591 local and 369 national research studies were used by the author [9].…”
Section: Introductionmentioning
confidence: 99%